Influence of sleep quality on clinical and laboratory parameters in women with polycystic ovary syndrome (Research, Society and Development, 2024)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrine disorder among women of reproductive age, characterized by hyperandrogenism, ovarian dysfunction and polycystic ovarian morphology. Objective: To describe the influence of sleep quality on clinical and laboratory parameters in women with polycystic ovary syndrome. Methodology: Integrative review, carried out in the Public Medline (PubMed) database, with DeCS/MESH descriptors “Polycystic Ovary Syndrome” and “Sleep”. Freely available articles were included, with research carried out on women with PCOS of any age group, published in the last five years, in Portuguese or English. Results: 66 studies were found and, after methodological screening, 5 were included in the review. In total, 279 women of varying ages were evaluated, of which those with PCOS and sleep disorders showed changes in body mass index, insulin resistance, liver fat and higher triglycerides (TG). Conclusion: The presence of sleep disorders in women with PCOS is associated with changes in symptoms and laboratory parameters. It is suggested, however, that more studies are needed to prove this relationship and the specific mechanisms.